STEM LEARNING ON ELECTRICITY USING ARDUINO-PHET BASED EXPERIMENT TO IMPROVE 8TH GRADE STUDENTS' STEM LITERACY - Tiara Diba Oktaviani, - (2017)
Technology is the application of scientific knowledge for practical purposes, especially in industry. One way to support the development of the technology is by integrating the use of technology and build the technology with the learning process in the form of STEM (science, technology, engineering, mathematics ) Learning approach. Applying STEM Learning could improve Students' STEM Literacy. The learning approach is applied in every aspect of Learning including the application of STEM Learning in the lesson plan and worksheet. The method that used in this research is weak experimental. One group class (N=15) taken and learn by STEM Learning approach. The topic that learned by students is the electricity topic which is separated into electrical circuit and electrical parameters. The learning process separated into 3 meeting and it is conducted once a week. 15 Students are given a test item before and after the lesson. There are 25 question that used to measure student STEM Literacy. The result of the normalized gain shows there are improvement in students' STEM Literacy. The most higher improvement is the students' technology literacy. Students' learn using the same technology in every meeting. That's influence students' technology literacy. ----Teknologi adalah penerapan ilmu pengetahuan untuk tujuan tertentu, terutama pada industri. Salah satu cara untuk mendukung perkembangan teknologi adalah dengan menintegrasikan teknologi dan membangun teknologi dalam proses belajar dalam bentuk pendekatan STEM ( ilmu pengetahuan, teknologi, tehnik, matematika). Dalam mengaplikasikan pendekatan STEM akan didapatkan kemampuan literasi STEM. Pendekatan ini diaplikasikan pada setiap aspek pembelajaran termasuk aplikasi pada rencana pembelajaran dan lembar kerja siswa. Metode yang di gunakan adalah weak experiment. Satu grup (N = 15) diambil dan diberikan kegiatan belajar mengajar dengan menggunakan Pendekatan STEM. Topic tang digunakan adalah kelistrikan yang dibagi menjadi Properti listrik dan rangkaian listrik. Proses belajar mengajar dibagi menjadi 3 pertemuan dan dilaksanakan sekali dalam seminggu. 15 orang siswa diberikan test sebelum dan sesudah belajar. Ada 25 soal yangdigunakan untuk mengukur kemampuan literasi STEM siswa. Hasil dari normalized gain menunjukan peningkatan kemampuan literasi STEM siswa. Peningkatan tertinggi terjadi pada literasi teknologi siswa. Siswa belajar dengan menggunakan teknologi yang sama pada setiap pertemuan. Ini adalah faktor yang mempengaruhi kemampuan literasi teknologi siswa .